Cefaleia pós-punção dural em cesariana: fatores de risco associados e novas perspectivas sobre condutas medicamentosas - SOUZA, Andrey Thiago Balieiro de (2022)
Objective: To conduct an integrative review about risk factors and new drug approaches for the prevention and control of post-spinal anesthesia headache in cesarean sections. Methods: Integrative review performed in PUBMED, SCIELO, BVS, Cochrane Library and Web of Science database, with descriptors: Post-Dural Puncture Headache, Cesarean section, Risk factors, Pre-anesthetic medication. 230 articles were found, 10 articles were used to build this work. Results: Among the 10 authors selected for the study, 50% (n=5) carried out the surveys analyzing the importance of the main risk factors that influence the incidence of Post-Dural Puncture Headache (PDPH), such as orientation and needle size, position that anesthesia is performed, number of attempts, among others. The other 50% (n=5) are about the influence of drug therapy on the symptoms and prevention of PDPH. Final considerations: The PDPH should be faced as a health public problem, so it’s understood the importance that further researches continues to be developed regarding this theme, in order to improve current prophylactic and therapeutic approaches, especially in pregnant women, who need to be in good general condition after a cesarean both to care and provide better contact with your baby.